Sudden severe hyperammonemia and status epilepticus -a case report- - Woo-Kyung Shin; Young-Eun Jang; Hannah Lee; Se-Hee Min; Ho-Geol Ryu (Korean Journal of Anesthesiology, 2013)
There are various causes to a low level of consciousness in patients in the intensive care unit. Neurological injury, infection, and metabolic disarray are considered as some of the causes. A 39 year-old female patient was transferred to our hospital with septic shock due to ascending colon perforation. The patient had previously received ovarian cancer surgery and a cycle of chemotherapy at another hospital. Emergent operation for colon perforation was successful. After the operation, she was treated in the intensive care unit for infectious and pulmonary complications. She suddenly showed deterioration in her level of consciousness and had a generalized seizure. At the time of her seizure, she had severe hyperammonemia. Brain CT showed severe cerebral edema that was absent in the CT scan taken 2 days before. Continuous renal replacement therapy was conducted but was ineffective in lowering the level of serum ammonia and the patient subsequently died.